COVID-19 and digital library services: an overview on legal information. Issue 1 (13th February 2021) - Peruginelli, Ginevra; Conti, Sara; Fioravanti, Chiara
Abstract : Purpose: The purpose of this paper is to investigate the initiatives providing legal information during the COVID-19 emergency, focusing on the fundamental role of digital libraries in creating, managing and sharing services to support and ensure access to legal information in times of emergency. Design/methodology/approach: To have an overall view of the legal information on COVID-19 available on digital libraries during the outbreak, a desk-research on the Web was conducted looking for both public and private sources of information. The selection of the sources was based on the type of information and services offered, the quality of information structuring, together with the data updating and the target users. Findings: The survey provided a huge and heterogeneous amount of legal information resources on COVID-19. The analysis on the source of information selected showed different kinds of approaches adopted by digital libraries in relation to types of information provided, information categorization, target audiences, purposes and services offered. Research limitations/implications: Two limitations have been identified: lack of previous studies in the domain and size of the samples cited. The conducted research should be seen as the "building block" upon which further research should be broadened and deepened. Limited samples are cited because of a rational choice; nevertheless, future research should be conducted also addressing a quantitative choice on identifying sources. Practical implications: The research proposes to give users practical guidance, namely, a first set of authoritative sources which gives legal information on COVID-19. Originality/value: This review paper could be seen as a first study on the issues related to accessing and sharing legal data at the time of the COVID-19; the research could be a starting point for devising a new form of communication of legal information in times of crisis.